Community perception on ‘third place’ generation and planning for enhanced neighbourhood interaction at Pengkalan Kubor, Malaysia - Mohd Azamli, Muhammad Iqmal; Sabil, Azmal; Abdul Rahim, Asiah; Asif, Nayeem; Ismail Jamail, Maliza (IOP Publishing Ltd, 2022)
Pengkalan Kubor at the east coast of Peninsular Malaysia is affected by limited neighbourhood interaction and liveability. A proper and good place is essential for neighbourhood interaction. There is a lack of places for social interaction, and the existing places are in poor condition and maintenance. This research aims to evaluate the impact of generating the "Third Place" to enhance neighbourhood interaction at Pengkalan Kubor. This paper seeks to identify the factors that obstruct neighbourhood interaction and evaluate the effectiveness of third place to resolve the neighbourhood interaction and improve the study context's liveability. The questionnaire survey used for this research evaluates neighbourhood interaction. Since the study area is in Pengkalan Kubor, the respondents selected for this study were within the community. In addition to defining the neighbourhood, the survey defined the third places within the study context. The findings from the public perception of neighbourhood interaction and third place at Pengkalan Kubor may be useful for many stakeholders for public places' future planning.